Revisiting teacher educators' training in Ethiopia: Implications for a new approach to curriculum development - Haftu Hindeya Gebremeskel; Ahmed Yibrie Ahmed; Dawit Asrat Getahun; Meskerem Lechissa Debele; Dawit Tibebu; Dereje Taye Wondem (Bahir Dar Journal of Education)
This study was a needs assessment study for developing MED curricula in Educational Sciences (teaching of mathematics and science subjects). It was aimed at understanding the current status of science and mathematics teaching particularly in Amhara Regional State, Ethiopia so as to identify the existing gaps in the preparation of primary school science and mathematics teachers and teacher educators for Colleges of Teacher Education (CTE). The study was qualitative in its design. A total of 37 participants (10 deans and vice-deans, 10 department heads, 6 teacher educators, 2 experts, 2 policy makers, 7 previous graduates) were purposely selected from five CTEs, two universities and from the Science and Mathematics Subjects Improvement Center at the Ministry of Education (MoE). Data were collected using semi-structured interview and focus group discussion. Furthermore, secondary data sources such as the National Learning Assessment results (MoE, 2000–2016), Education Sector Development Program documents (2010–2015), Growth and Transformation Plan I (GTP I) (MoFED, 2010) and GTP II (National Plan Commission, 2016), previous MEd curricular documents in science and mathematics education, as well as existing research outputs were examined. Results indicated very low student performance in mathematics and science disciplines, CTE teacher educators’ lack of sufficient and relevant pedagogical background as they did not pass through relevant training programs. They reported they have sufficient subject matter knowledge but in pure disciplines that are not very much relevant for someone who pursues a career as a teacher educator. Furthermore, traditional nature of content delivery, use of assessment merely for grading purposes, and deviation of assessment from the Minimum Learning Competencies (MLC) designated for the level are depicted as problems. The obtained results in general show a clear gap in the general pedagogical knowledge and skills, pedagogical content knowledge, and instructional technology that demanded the need of following the framework that integrates technology, pedagogy, and content knowledge for the development of new curricula.